Prolonging Ultralong Organic Phosphorescence Lifetime to 2.5 s through Confining Rotation in Molecular Rotor. Issue 10 (25th February 2019) - Li, Mengping; Ling, Kun; Shi, Huifang; Gan, Nan; Song, Lulu; Cai, Suzhi; Cheng, Zhichao; Gu, Long; Wang, Xuan; Ma, Chaoqun; Gu, Mingxing; Wu, Qi; et al.
Abstract: Developing ultralong organic phosphorescence (UOP) materials has become a growing concern. To date, it remains a formidable challenge to prolong the lifetime of ultralong phosphorescence under ambient conditions. A series of fluoro‐substituted phenylboronic acid derivatives with UOP feature under ambient conditions is reported here. The UOP lifetime of 2, 4‐difluorophenylboronic acid (24FBP) crystal is up to 2.50 s, which is the longest emission lifetime among the reported single‐component pure organic phosphors. Combining the experimental and theoretical study, upon stabilization of triplet excitons by H‐aggregation, it is reasoned that rotation confinement in molecular rotors plays a critical role in prolonging the UOP lifetime. Given the feature of ultralong luminescence, 24FBP phosphor is successfully applied to anticounterfeiting. This result will pave the way toward tuning the UOP lifetime and expanding the scope of metal‐free organic phosphorescent materials with ultralong luminescence and their applications. Abstract : Ultralong organic phosphorescence of 2, 4‐difluorophenylboronic acid with a lifetime of up to 2.5 s is obtained by suppressing nonradiative transitions with rotation confinement in fluoro‐substituted phenylboronic acid derivatives under ambient conditions, which is successfully applied to anticounterfeiting.